Predatory Property: Urban Land Acquisition, Housing and Class Formation in Tiruppur, South India. (December 2015) - De Neve, Geert
While liberalization policies have unleashed unprecedented opportunities for accumulation and wealth extraction in India, the urban social consequences of post-reform economic restructuring have been poorly documented to date. Based on ethnographic research carried out in the city of Tiruppur in South India, this article describes the processes of land acquisition and politics of housing that shape the contemporary dynamics of urban restructuring and class formation in this industrial city. The article describes how a powerful caste not only profited from rapid industrial accumulation, but in the process also came to monopolize the urban property market and real estate industry. Moreover, this new urban elite mobilizes urban property in the competitive pursuit of status and distinction through which they seek to establish themselves as an urban, industrial class. It is argued, first, that such processes of wealth accumulation and status competition have led to the dispossession of the urban working classes from home ownership in the city and, second, that urban property plays a key role in the transformation of urban class relations and in the production of a property-less labouring class that is kept under increasingly precarious and uncertain living conditions in the city.